DI-089 The mothif study or how to implement a pharmacist network in haemostasis to assess the costs of treatment in haemophilia a and b. (25th February 2017) - Horvais, V; Pennetier, M; Chapelle, G; Athouel, A; Bauer, S; Cogulet, V; Lebert, C; Clerc, MA; Vincent, I
Abstract : This abstract was published in error and withdrawn at the author's request.